2013
DOI: 10.1007/s10803-013-1942-4
|View full text |Cite
|
Sign up to set email alerts
|

“In the Driver’s Seat”: Parent Perceptions of Choice in a Participant-Directed Medicaid Waiver Program for Young Children with Autism

Abstract: This study investigated families' experience of choice within a participant-directed Medicaid waiver program for young children with autism. Fourteen parents or grandparents participated in in-depth interviews about their experience of choosing personnel, directing in-home services, and managing the $25,000 annual allocation. Key findings included families' preference to hire providers with whom they have a prior relationship, parent empowerment and differences of opinion about parents as teachers. Professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 17 publications
3
50
0
1
Order By: Relevance
“…, Mitchell , Timberlake et al . ); one included the perspectives of a combination of family members or caregivers and service providers (Dew et al . ); and two articles explored the perspectives of service users who had support from parents or guardians when necessary (Mitchell , Lombe et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, Mitchell , Timberlake et al . ); one included the perspectives of a combination of family members or caregivers and service providers (Dew et al . ); and two articles explored the perspectives of service users who had support from parents or guardians when necessary (Mitchell , Lombe et al .…”
Section: Resultsmentioning
confidence: 99%
“…Six of the eleven research articles (Mitchell ,b,c, ,b, Timberlake et al . ) focused specifically on self‐directed policy for young people with disability. The three review articles aimed to synthesise research from the perspectives of programme administrators and service users, and placed findings within the context of government and service delivery policy in the United Kingdom (Harkes et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the life course, Medicaid influences family caregiving experiences through its role as the primary funding stream for LTSS. In childhood, parents of children with disabilities may act as coordinators of services and evaluators of quality, as one study of parents of children with autism spectrum disorder found (Timberlake, Leutz, Warfield, & Chiri, 2014). In adulthood, Medicaid offers an opportunity for greater autonomy and self-direction, for all program recipients, including people with mental illness, people with IDDs, and older adults, populations previously thought unable or uninterested in decision making (San Antonio et al, 2010;Shen et al, 2008).…”
Section: State and National Policiesmentioning
confidence: 99%